Geomorphometry : concepts, software, applications - Hengl, Tomislav; Reuter, Hannes I. (Elsevier, 2009)
Geomorphometry is the science of quantitative land-surface analysis. It draws upon mathematical, statistical, and image-processing techniques to quantify the shape of earth's topography at various spatial scales. The focus of geomorphometry is the calculation of surface-form measures (land-surface parameters) and features (objects), which may be used to improve the mapping and modelling of landforms to assist in the evaluation of soils, vegetation, land use, natural hazards, and other information. This book provides a practical guide to preparing Digital Elevation Models (DEM) for analysis and extracting land-surface parameters and objects from DEMs through a variety of software. It further offers detailed instructions on applying parameters and objects in soil, agricultural, environmental and earth sciences. This is a manual of state-of-the-art methods to serve the various researchers who use geomorphometry.- Resumé vydavatel
"Provides a practical guide to preparing DEMs [Digital Elevation Models] for analysis and to extracting land surface parameters and objects from DEMs through a variety of software"--Page 4 of cover.
"European Commission, Directorate General, Joint Research Centre, IES, Institute for Environment and Sustainability"--Page 4 of cover.
Keywords: geomorfologie; mapování; geografické informační systémy; modelování a simulace; půdní mapy; geomorphology; mapping; geographical information systems; modeling and simulation; soil maps; elektronické knihy; sborníky; electronic books; papers of several authors